2014
DOI: 10.1080/10810730.2013.821561
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Public Resistance to Messages About Health Disparities

Abstract: Advocates and policymakers strategically communicate about health disparities in an effort to raise public awareness, often by emphasizing the social and economic factors that influence these disparities. Previous research suggests that predisposing political orientation and values related to self-reliance and personal responsibility may produce resistance to such messages. In this study, the authors culled 4 messages about the causes of disparities in life expectancy from public discourse and randomly present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 59 publications
1
53
1
Order By: Relevance
“…Such items have been used in other work establishing the persuasive potential of health messages. 2225 …”
Section: Methodsmentioning
confidence: 99%
“…Such items have been used in other work establishing the persuasive potential of health messages. 2225 …”
Section: Methodsmentioning
confidence: 99%
“…These leanings are even more closely aligned with political parties when using implicit measures of party affiliation (Hawkins & Nosek, 2012). For this reason, recent work investigating the role of values and political orientation in message processing considers party leaners as partisans (Gollust & Cappella, 2014). The GfK data showed that 151 of the 168 participants who did not identify as one or the other, but rather as Independent, were considered party leaners; that is, the 151 participants identified themselves as either Republicans or Democrats when they were further asked, "Do you think of yourself as closer to the .…”
Section: Methodsmentioning
confidence: 99%
“…Respondents were also less aware of health disparities by race than by income (Booske, Robert, & Rohan, 2011). Among a group of nationally representative U.S. adults, predisposing values toward personal responsibility and political orientation account for some differences in reactions to messages about health disparities (Gollust & Cappella, 2014). Researchers and clinician soften identify personal responsibility and behavior as the natural starting point for health discourse, assumptions that resonate with values implicit in the “American Dream” (Lundell, Niederdeppe, & Clarke, 2013).…”
Section: Rationale and Theoretical Underpinningsmentioning
confidence: 99%